Prophetic Theology in Black Theology, with special reference to the Kairos document - Vellem, Vuyani S. (HTS teologiese studies, 2010)
The ‘Protest’ and ‘Confessing’ Models in the streams of Black Theology of liberation provide a creative link between the Prophetic Theology in the Kairos document (KD) and the Black Theology of liberation. Launched in a distinct moment of history – an ‘opportune moment’ – the KD propagated the best responses among some and the worst among others as a rapturous critique of State and Church theologies. In this article, I argued that the KD, which remains a version of liberation theology par excellence, offers a methodology that is still appropriate to our democratisation processes in South Africa. The KD is the product of a theology that did not only expand the contours of traditional theology, but also understood confession as a political praxis. Thus, the interest of the poor should still mitigate forth-telling in our democratic vision in dialogue inspired by the alluring prophetic vision of an alternative community based on the principles of the reign of God.